Treatment of the real boiler cleaning wastewater in an anaerobic fluidized bed microbial fuel cell: Organic matter degradation, bioelectrochemistry, and kinetics. (21st August 2019) - Wang, Jiating; Liu, Xinmin
Abstract : A single chambered air cathode anaerobic fluidized bed microbial fuel cell (AFB‐MFC) was simultaneously used to dispose of the real boiler cleaning wastewater (BCW) containing a high concentration of citric acid and to generate renewable energy. At the temperature of 40 °C and flow rate of 5.22 mL/s, the removal efficiency and power density were improved in AFB‐MFC with the abiotic cathode of the Pt/C modified carbon cloth. With the real boiler cleaning wastewater fed as substrate, the maximal removal efficiency of chemical oxygen demand (COD) in AFB‐MFC was up to 90 %, which was higher than the corresponding value of 84 % obtained in the anaerobic biological fluidized bed reactor (ABFBR). The maximum voltage and the maximum power density were 424.6 mV and 18.68 mW/m 2, respectively, when the external resistance was 5000 Ω. Furthermore, the Haldane inhibition model was well fitted with experiment data (R 2  = 0.97–0.98) in AFB‐MFC/ABFBR. The inhibition of citric acid degradation in ABFBR was stronger than that of AFB‐MFC. The bioelectrochemical system of AFB‐MFC not only improved the charge transfer and but also accelerated the reaction rate of citric acid. The reduction of the ferric ion and oxidation of ferrous ion in AFB‐MFC played important roles in the degradation reaction of critic acid.